2006
DOI: 10.1128/jb.00462-06
|View full text |Cite
|
Sign up to set email alerts
|

General Mutagenesis of F Plasmid TraI Reveals Its Role in Conjugative Regulation

Abstract: Bacteria commonly exchange genetic information by the horizontal transfer of conjugative plasmids. In gram-negative conjugation, a relaxase enzyme is absolutely required to prepare plasmid DNA for transit into the recipient via a type IV secretion system. Here we report a mutagenesis of the F plasmid relaxase gene traI using in-frame, 31-codon insertions. Phenotypic analysis of our mutant library revealed that several mutant proteins are functional in conjugation, highlighting regions of TraI that can tolerate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
42
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 45 publications
4
42
0
Order By: Relevance
“…To evaluate the principle of how imbalanced expression of substrate and receptor genes might affect T4 secretion, we instead returned to the well-characterized F system. Overexpression of the F traI gene in trans to the wild-type conjugation genes causes a negative dominant phenotype for conjugation (30). That negative effect is also visible in our experiments where pOX38 transfer was reduced by 66-fold in the presence of a plasmid expressing Cre-TraI F compared to Cre alone (Fig.…”
Section: Vol 193 2011 Type IV Secretion By C Fetus Subsp Venerealsupporting
confidence: 67%
“…To evaluate the principle of how imbalanced expression of substrate and receptor genes might affect T4 secretion, we instead returned to the well-characterized F system. Overexpression of the F traI gene in trans to the wild-type conjugation genes causes a negative dominant phenotype for conjugation (30). That negative effect is also visible in our experiments where pOX38 transfer was reduced by 66-fold in the presence of a plasmid expressing Cre-TraI F compared to Cre alone (Fig.…”
Section: Vol 193 2011 Type IV Secretion By C Fetus Subsp Venerealsupporting
confidence: 67%
“…High levels of TraD led to lower ColE1 mobilization frequencies with the pOX38⌬oriT⌬traD derivative than were observed without overexpression. Inhibition of the pOX38 transfer system by an imbalance of traD and traI expression has been reported earlier (66,67). Importantly, however, increased TraD concentrations eliminated the requirement for oriT R1 in ColE1 transfer such that wild-type frequencies of mobilization by the R1-16⌬oriT⌬traD derivative were observed regardless of the source of traD.…”
Section: Resultsmentioning
confidence: 92%
“…These are the cases of the TraY of F plasmid (34), TrwA of R388 (33), MbeC of ColE1 (49), and MobC of pC221 (42). In other cases, like TraI of plasmid F, TraA of pIP501, and Mob of pBBR1 (19,22,47), it has been shown that expression of the relaxase gene is negatively regulated at the transcriptional level by the activity of the relaxase protein itself. However, the interactions between the relaxase and the host RNA polymerase (RNAP) at the plasmid origin of transfer (oriT) remain to be investigated.…”
mentioning
confidence: 99%